Civilizations beyond earth : extraterrestrial life and society - Vakoch, Douglas A.; Harrison, Albert A. (Berghahn Books, 2011)
Astronomers around the world are pointing their telescopes toward the heavens, searching for signs of intelligent life. If they make contact with an advanced alien civilization, how will humankind respond? In thinking about first contact, the contributors to this volume present new empirical and theoretical research on the societal dimensions of the Search for Extraterrestrial Intelligence (SETI). Archaeologists and astronomers explore the likelihood that extraterrestrial intelligence exists, using scientific insights to estimate such elusive factors as the longevity of technological societie.